2017
DOI: 10.1002/jmv.24844
|View full text |Cite
|
Sign up to set email alerts
|

ITPA gene polymorphism (94C>A) effects on ribavirin‐induced anemia during therapy in Egyptian patients with chronic hepatitis C

Abstract: Inosine triphosphatase (ITPA) gene variants can protect against ribavirin (RBV)-induced anemia in patients treated for chronic hepatitis C. The aim of this study was to determine the relationship between genetic variants of ITPA polymorphism, anemia, RBV dose reduction, and treatment response in hepatitis C virus (HCV)-infected patients. This study was conducted on 97 Egyptian chronic HCV patients who were scheduled for pegylated-interferon (PEG-INF) /RBV therapy. ITPA genotypes rs1127354 were determined by Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Studies showed that the proportion of patients who completed the planned ribavirin treatment in non‐CC patients was significantly higher than that of patients with CC 30,33 . This result is consistent with the conclusion that the incidence of haemolytic anaemia in patients with non‐CC type ITPA rs1127354 is relatively low, and the level of haemoglobin is reduced.…”
Section: Discussionsupporting
confidence: 84%
“…Studies showed that the proportion of patients who completed the planned ribavirin treatment in non‐CC patients was significantly higher than that of patients with CC 30,33 . This result is consistent with the conclusion that the incidence of haemolytic anaemia in patients with non‐CC type ITPA rs1127354 is relatively low, and the level of haemoglobin is reduced.…”
Section: Discussionsupporting
confidence: 84%
“…Table S1 summarises the collection of exonic variants that are more confidently dominance fine-mapped. The non-additive signal in the ITPA locus associated with red blood cell distribution width was fine-mapped to rs1127354, a non-synonymous single nucleotide variant which is known to predict drug induced anaemia among chronic HCV patients (39)(40)(41)(42)(43). The genome-wide significant non-additive association with hearing difficulty/problems was fine-mapped to rs2877561, a synonymous change in ILDR1 associated with age-related hearing impairment (44) but which did not reach genome-wide significance in that study.…”
Section: Application: Fine-mapping Dominance Locimentioning
confidence: 99%
“…Retinal hemorrhage is also a typical finding of anemia or thrombocytopenia in retinopathy. IFN-based therapies and RBV have dose-dependent side effects of anemia and thrombocytopenia [22][23][24][25][26][27][28]. Our study revealed a higher incidence of anemia and thrombocytopenia in the HCV-treated cohort.…”
Section: Discussionmentioning
confidence: 59%